Neuroergonomics Applications of Electroencephalography in Physical Activities: A Systematic Review - Rahman, Mahjabeen; Karwowski, Waldemar; Fafrowicz, Magdalena; Hancock, Peter A. (Frontiers in Human Neuroscience, 2019)
In recent years, interest has grown in physical neuroergonomics, a sub-field of ergonomics that investigates the brain activities of people engaged in diverse physical activities. The present work extends upon prior assessments of the state of this art, but here we narrow the focus specifically to studies using electroencephalography (EEG) to measure brain activity, correlates, and effects during physical activity. The review uses systematically selected openly published works derived from a guided search through peer-reviewed journals, conference proceedings, dissertations, and theses. Identified studies were then categorized by the type of physical activity and evaluated according to the identified objectives, methods, and findings via statistical and content-based analyses. From the initially identified works (n=114), a specific number (n=34) focused on low-intensity muscular activities, while an additional group (n=34), featured both physical and cognitive tasks. The remainder (n=46) investigated various physical exercises and activities and so were here identified as a miscellaneous grouping. Most physical activities were isometric/isotonic exertions, finger movements, walking, and cycling. Further directed analyses using factors such as participants’ gender, EEG recording devices, data processing, and artifact correction methods, were conducted upon the literature identified. Finally, contemporary research gaps in physical neuroergonomics were identified and ways to address such gaps are discussed.